Local Practices in Sacred Groves Management in Togo: A Comparative Study in Nawda, Ifè, and Ouatchi Lands - Ekoue, Akouete Gale; Sama, Nankpakou; Yodo, Amavi; Adjonou, Kossi; Kossi-Titrikou, Komi; Kokou, Kouami (European Scientific Journal, ESJ, 2024)
Local populations have ensured the sustainable management of forest resources by sanctifying areas of woodland. Despite the reduction of these sacred groves by multiple threats, including those caused by humans, they persist and demonstrate the community’s desire for preservation. This paper focuses on increasing the comprehension of the management of local sacred groves within the Nawda, Ifè, and Ouatchi regions in Togo. Qualitative ethnographic analysis was employed to describe how the management practices are carried out and also to examine their underlying socio-cultural concepts. The findings of the study indicate that customary religious, family, and political authorities manage sacred groves. Management practices involve conducting ritual ceremonies and establishing rules and regulations. The socio-cultural representations that shape these management practices facilitate the definition of sacred groves as sites of shared memory, confer upon them the status of dwelling places of protective divine beings/ancestors, and identify them as sources of prosperity and abundance.